A Poetic Death — the Literary Images of Suicidal Deaths in the Literature of Nineteenth Century - Kaźmierska, Anna (Wzniosłość i makabra w literackich obrazach śmierci, 2014)
There exists something like beautiful life. Is it possible to die beautifully? Is there a beauty that canbe related to something as terrifying as suicidal dying? The study presents attempts of making the deathpoetic by the characters that emerged in opuses of the authors of the nineteenth century. The paper showsthe reasons why these characters tried to die in a sophisticated way, which cannot be trivial at all. Theauthor of this study attempts to explain why they make their death look like a performance. And thenumber of viewers is not the most important issue they are worrying about. What is really meaningfulis to tear the constraints which are imposed by society, culture, people’s demands and to achieve theliberation from life’s and death’s schemes. The main premise of the paper is that, for all characters, thesuicidal death is most of all the manifestation of their own need to decise about themselves and to explorean art in every detail of people’s existence. The discussed phenomena are illustrated in the novels ofHenryk Sienkiewicz, Gabriela Zapolska and Włodzimierz Perzyński.